Swine Flu (Influenza A, H1N1pdm2009) Infection on an Elderly Patient with Chronic Obstructive Pulmonary Disease (COPD): A Case Report - Anak Agung Bagus Bramardipa; Anak Agung Gde Upeksha (Jurnal Respirasi, 2023)
Introduction: Influenza is one of the most common causes of respiratory illness in the world. In April 2009, a novel H1N1 virus of swine origin was spreading among individuals, and within days became a pandemic, called H1N1pdm2009. Years after the pandemic, H1N1pdm2009 is now a common seasonal flu that manifests as flu-like symptoms just like other influenza. Swine flu is a self-limiting disease that doesn’t need necessary antiviral treatment unless it displays moderate presentation or in an individual with comorbidities.